The level of time management skills among students of the Faculty of Physical Education, Tishreen University (Journal of Hama University, 2024)
The aim of the research is to identify the level of time management skills among students of the Faculty of Physical Education at Tishreen University. The researcher used the descriptive survey method, and the study sample consisted of (200) male and female students from the Faculty of Physical Education at Tishreen University. The questionnaire was used as a data collection tool, designed by Al-Momani (2017), consisting of (35) items distributed over four skills (planning-to organiz-direction-control). The results of the research concluded that the level of time management skills among students of the Faculty of Physical Education at Tishreen University was acceptable, in addition to the absence of gender differences in the level of time management skills.
Keywords: time management. Students of the College of Physical Education